Просвітницька діяльність української інтелігенції в таборах для переміщених осіб у західних окупаційних зонах (1944–1951 рр.) - Стрільчук, Людмила; Strilchuk, Lyudmyla (My University, 2016)
У статті проаналізовано просвітницьку діяльність українців, які перебували в таборах для Переміщених осіб у західних окупаційних зонах наприкінці Другої світової війни й після її завершення. Вимушені чекати вирішення питання про переселення, українці не лише зуміли зорганізувати свій побут у таборах для ПО, але й налагодити національно-культурне життя, шкільництво. В авангарді цього процесу стояла українська інтелігенція.The article analyzes outreach and awareness-raising activity of the Ukrainians in the camps for the displaced persons in the Western occupation zones at the end of the World War II and after it. Among those half-million Ukrainians who chose the way of political escape there were many of those who belonged to the Ukrainian intelligenzia: scientists, teachers, bishops, writers, doctors and artists. Majority of them came from the Western Ukraine where «Prosvita» society always enjoyed authority. It is because of this why the framework for this society was used as a basis for the national, educational and cultural activity of the Ukrainians during their stay at the camps for the displaced persons.
Outreach and Awareness-raising Activity of the Ukrainian Intelligenzia in the Camps for Displaced Persons in the Western Occupation Zones (1944-1951)
Keywords: просвітницька діяльність; українська інтелігенція; переміщені особи; культура; outreach and awareness-raising activity; Ukrainian intelligenzia; «Просвіта» society; displaced persons; culture; education; national idea; Western occupation zones